KEEFEKTIFAN MODEL PROBLEM-SOLVING BERBANTUAN MEDIA CROSSWORD PUZZLE TERHADAP PEMAHAMAN KONSEP SISWA PADA PEMBELAJARAN MATERI GAYA - Umami, Ulfa; Purwanti, Kartika Yuni (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This research aims to find out how science learning is implemented by applying the Problem-Solving Model assisted by Crossword Puzzle media in improving the quality of student learning at SDN Bandungan 01. The methodology used is quantitative and in the form of an experiment, namely quasi-experimental with the type of field study. Data collection techniques use population and sample techniques. And the data analysis technique used in this research is a data collection technique that uses a test technique of score results from the pretest and posttest. With concrete or real media, it is easy for students to find solutions to the problems given. The effort used to improve students' concept understanding is to apply a problem-solving learning model with the help of Crossword Puzzle media which will be collaborated with science and science learning materials. The conclusion of this research is that it can be concluded that the use of the problem solving model assisted by crossword puzzle media makes a significant contribution in increasing the conceptual understanding of fourth grade students at SD Negeri Bandungan 01.